2016
DOI: 10.1007/s10120-016-0637-x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of clinical tumor–node–metastasis staging on survival in gastric carcinoma patients receiving surgery

Abstract: Background Preoperative clinical staging of gastric cancer is used to determine therapeutic strategies. However, the impact of the clinical stage on survival has not been completely investigated, although the relationship between pathologic staging and survival outcome has been reported. The aim of the present study was to clarify the predictability of patient survival based on clinical staging and to evaluate the usefulness of staging as an indicator for selecting the treatment modality. Methods A total of 30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 36 publications
1
22
0
2
Order By: Relevance
“…We have previously published the prognostic impact of clinical staging of gastric cancer based on the 7th TNM [12]. Also in this study, our results showed the excellent prognostic impact of the cStage proposed in the 8th edition of the TNM classification.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…We have previously published the prognostic impact of clinical staging of gastric cancer based on the 7th TNM [12]. Also in this study, our results showed the excellent prognostic impact of the cStage proposed in the 8th edition of the TNM classification.…”
Section: Discussionsupporting
confidence: 68%
“…The preoperative invasion depth (cT), lymph node metastasis (cN), and distant metastasis (cM) were determined in accordance with a previously published report [12]. A brief summary is presented below.…”
Section: Criteria For Determining Preoperative Clinical Tumor Progresmentioning
confidence: 99%
See 1 more Smart Citation
“…The AJCC eighth edition also provides an alternative clinical stage prognostic table derived from surgically treated patients treated at Shizouoka Cancer Center (Japan) [14,15]. The use of two data sources provided validation for our clinical stage grouping schema with excellent separation of stage groups from both sources while highlighting differences in prognosis based on clinical stage derived from all patients or only surgical patients and by differences in the patient population (US versus Japanese patients).…”
Section: Discussionmentioning
confidence: 99%
“…There were 46 cases in the gastric antrum/pylorus, 36 cases in gastric fundus/cardia and 23 cases in the gastric body. Additionally, the tumor-node-metastasis (TNM) stages of all patients were assessed (13). There were 46 patients with TNM stage II and 59 patients had stage III.…”
Section: Patientsmentioning
confidence: 99%